2008
DOI: 10.1002/hed.20837
|View full text |Cite
|
Sign up to set email alerts
|

Supracricoid partial laryngectomy as salvage surgery for radiation therapy failure

Abstract: Background. The main concern in the treatment of laryngeal carcinomas is tumor control with preservation of laryngeal functions. We believe that salvage supracricoid partial laryngectomy (SPL) should be carefully considered in selected cases of radiotherapy failure, because it can offer the possibility of achieving adequate tumor control with preservation of laryngeal functions.Methods. A series of 31 patients who underwent an SPL as salvage procedure after radiotherapy failure was reviewed.Results. Locoregion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 49 publications
(57 reference statements)
1
49
0
Order By: Relevance
“…Despite contacting and receiving replies from most of the authors, multiple studies did not have the individual data points required to calculate OS and DFS for meta‐analysis. As a result, only three studies (including 103 elective necks and 52 observed) were used for the meta‐analysis for OS . Meaningful DFS could not be calculated due to insufficient data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite contacting and receiving replies from most of the authors, multiple studies did not have the individual data points required to calculate OS and DFS for meta‐analysis. As a result, only three studies (including 103 elective necks and 52 observed) were used for the meta‐analysis for OS . Meaningful DFS could not be calculated due to insufficient data.…”
Section: Resultsmentioning
confidence: 99%
“…The available data were limited, heterogeneous, and inconsistently reported, but these patients did tend to die from their disease recurrence and could not be salvaged. Of the four included studies with these data, only one of 14 patients with a regional recurrence after an observed neck had long‐term survival (5‐year OS = 7%) . Other included studies showed equivalent rates of regional recurrence between END and observed necks, or even greater rates in END patients, without report of their survival …”
Section: Discussionmentioning
confidence: 99%
“…22 Laryngeal preservation rates for SCPL in the salvage setting have been shown to be around 90%. 23 TLM is well established in the primary management of early-stage larynx cancer. 24 The 5-year disease-free survival rate in early-stage glottic cancer treated primarily by TLM is 81% to 93%.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports indicate an incidence of 10-28 per cent occult neck metastasis in persistent and recurrent laryngeal disease after primary RT. [6][7][8][9] Accurate restaging with scrupulous reassessment of the nodal status cannot completely rule out the presence of occult neck disease. [10][11][12] Small nodal metastases are still a diagnostic challenge despite continuing improvements in imaging techniques.…”
Section: Introductionmentioning
confidence: 99%